THE EXISTENCE OF AN IMMIGRANT IN HAMILTON: THE REVOLUTION (2015): A PLAY SCRIPT BY LIN- MANUEL MIRANDA AND JEREMY MCCARTER - Mona Zamrika Putri; Kurnia Ningsih; Desvalini Anwar (Universitas Negeri Padang, 2018)
The purpose of this analysis is to expose the issue of the existence of an immigrant through the analysis of the literary devices such as plot, setting. This analysis is related to the concept power and knowledge by Michel Foucault and consciousnessby Sigmund Freud, supported by the text and context based interpretation. The result of the analysis shows that the immigrant’s struggles to prove his existence which reflected through his efforts in showing loyalty towards the country and his mindset about the issue in the country.